Implementasi Pembelajaran Berbasis Karakter di Masa Pandemi Covid 19 (Studi di Sekolah Dasar Negeri Binjai) - Dina Puspita; Akrim Akrim; Nurmadiah Nurmadiah (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2023)
The purpose of this study is to analyze in depth the character-based learning that was carried out during the covid 19 pandemic at SD Negeri 0223904 North Binjai, to analyze in depth how SD Negeri 0223904 North Binjai implements character-based learning with the Blended learning model and to find out the impact of the character-based learning model implemented by students at SD Negeri 0223904 North Binjai. The research approach uses qualitative data sources from school principals, teachers, students and parents. Research findings (1) the implementation of character education in schools during the covid 19 pandemic was carried out in the following ways (a) Character learning was carried out by developing the Binjai city teachers' KKG program, (b) Learning was carried out through blended learning, (c) Instilling positive habits both at school and in the classroom, (d) Implemented in an integrated manner with each lesson through lesson plans and learning programs, (e) Involve the participation of the school community; (2) Learning the blended model at SD Negeri 0223904 Binjai is considered very effective, out of 365 students, 117 students (32.05%) chose to use only online learning, while 189 students (51.78%) tended to choose blended and 59 students (16.16%) did not choose any form of learning. Based on this data it can be said that students like blended learning, namely 51.78%. This is because students are willing to accept blended learning by means of a combination of face-to-face and online as well as the existence of internet package funding assistance from schools in the form of deductions from school fees. In addition, students really like blended learning because learning is interesting, fun and not boring